2012
DOI: 10.1363/3703411
|View full text |Cite
|
Sign up to set email alerts
|

Stability and Change in Fertility Preferences Among Young Women in Malawi

Abstract: Fertility preferences are important measures for forecasting fertility, calculating levels of unwanted or mistimed fertility and assessing unmet need for contraceptives. One of the assumptions underlying the use of fertility preferences for these objectives is that they are relatively stable over time.1 However, in Sub-Saharan Africa-where fertility, both desired and actual, remains comparatively high and childbearing patterns are increasingly heterogeneousfertility preferences are likely to be unstable.* Very… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
15
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 24 publications
(36 reference statements)
1
15
0
Order By: Relevance
“…Confirmed or suspected HIV infection, for example, leads women to accelerate their childbearing plans in order to achieve their ideal family size while still in good health (Trinitapoli and Yeatman ), while caregiving responsibilities for non‐biological children (fostering) often lead women to reduce their numeric preferences and delay their childbearing (Bachan ). Labor market opportunities may lead women to adjust their timing preferences (Sennott and Yeatman ), while expectations that any serious relationship would be solidified through offspring mean that partnership changes in the wake of death or divorce tend to increase desired fertility (Verheijen ; Yeatman et al. ).…”
Section: Uncertainty and Strategic Flexibilitymentioning
confidence: 99%
See 2 more Smart Citations
“…Confirmed or suspected HIV infection, for example, leads women to accelerate their childbearing plans in order to achieve their ideal family size while still in good health (Trinitapoli and Yeatman ), while caregiving responsibilities for non‐biological children (fostering) often lead women to reduce their numeric preferences and delay their childbearing (Bachan ). Labor market opportunities may lead women to adjust their timing preferences (Sennott and Yeatman ), while expectations that any serious relationship would be solidified through offspring mean that partnership changes in the wake of death or divorce tend to increase desired fertility (Verheijen ; Yeatman et al. ).…”
Section: Uncertainty and Strategic Flexibilitymentioning
confidence: 99%
“…5 Other analyses using TLT data have shown that women's numeric and timing preferences changed over time in patterned ways, most predictably by relationship changes and economic factors (Sennott and Yeatman 2012;).…”
Section: Notesmentioning
confidence: 99%
See 1 more Smart Citation
“…Two studies, one from Ghana and one from Morocco, found that approximately two-thirds of women provided different responses to ideal family size questions over their respective two- and three-year reference periods (Bankole and Westoff 1998; Debpuur and Bawah 2002). Other studies from Africa have found that changes in the desire for more children and the desired timing of children are common (Kodzi et al 2010; Sennott and Yeatman 2012). …”
Section: Introductionmentioning
confidence: 99%
“…In contexts of uncertainty, women's fertility preferences and behaviors are flexible, dynamic over time, and responsive to social milieus and networks (Entwisle et al. ; Sandberg ; Sennott and Yeatman ; Trinitapoli and Yeatman ; Yeatman, Sennott, and Culpepper ). Attitudes toward and use of contraception change as relationships shift and evolve (Adetunji ; Anglewicz and Clark ).…”
mentioning
confidence: 99%